2018
DOI: 10.1111/jch.13325
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years of LIFE (Losartan Intervention for Endpoint Reduction in Hypertension)—Lessons learned for losartan: An “old dog playing good tricks”

Abstract: There is an unmet need to prevent cardiovascular disease and chronic kidney disease development and progression worldwide. Losartan, the first angiotensin receptor blocker, was shown to exert significant cardioprotective and renoprotective effects in the LIFE (Losartan Intervention for Endpoint Reduction in Hypertension) and RENAAL (Reduction of Endpoints in NIDDM With the Angiotensin II Antagonist Losartan) trials. Losartan significantly prevented stroke and decreased serum uric acid levels and the rates of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 68 publications
0
12
0
1
Order By: Relevance
“…The reduction of a40 proceeded smoothly, yielding b40 in excellent yield. Continuing with our exploration of late‐stage reductions, we used the losartan derivative a41 ; losartan is a medication used to treat high blood‐pressure, in some cases for diabetic kidney disease and hearth failure; a41 was reduced in very good yield. Quinine modification afforded a42 , and its reduction produced the corresponding sulfide b42 as the sole product in excellent yield; quinine is an antimalarial used mainly for infections produced by Plasmodium Falciparum , which is resistant to chloroquine or when other drugs are not available .…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of a40 proceeded smoothly, yielding b40 in excellent yield. Continuing with our exploration of late‐stage reductions, we used the losartan derivative a41 ; losartan is a medication used to treat high blood‐pressure, in some cases for diabetic kidney disease and hearth failure; a41 was reduced in very good yield. Quinine modification afforded a42 , and its reduction produced the corresponding sulfide b42 as the sole product in excellent yield; quinine is an antimalarial used mainly for infections produced by Plasmodium Falciparum , which is resistant to chloroquine or when other drugs are not available .…”
Section: Resultsmentioning
confidence: 99%
“…The LIFE study and its additional analysis demonstrated the results according to which the presence of LVH and left bundle branch block signs on ECG increases the risk of cardiovascular death by 1,6 times, sudden cardiac death -by 3,4 times and hospital admission rate for heart failure -by 1.7 times [15].…”
Section: Original Researchmentioning
confidence: 97%
“…Perioperative management of ANG II-related medication is debated (21). Reducing ANG II has significant clinical relevance in managing hypertension and heart failure and angiotensin II type 1 receptor (AT 1 R) blockade has been shown to have renoprotective properties (22). Still, it is common clinical practice to discontinue ongoing ANG II-related medication preoperatively to avoid and reduce hypotensive events, which are more prominent in patients with continued treatment (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%